A Review of Infiltration Excess Overland Flow (IEOF): Terms, Models and Environmental Impact - Siti Nurbaidzuri, Reli @ Raily; Izham, Mohamad Yusoff; Muhamad Uznir, Ujang; Habibah, Lateh (CIRWORLD, 2016)
High precipitation rate usually give an impact on soil instability and streamflow volume that lead to hazard such as landslide, soil erosion and flood. However, such hazard might happen as a result of various factors including types of soil, soil structure, land used, human activities and surface and subsurface water flow. The major changes on flow rate might change the soil structure and flow direction due to high volume of precipitation with uneven dispersion, especially in hilly topography. The research on Streamflow Generating Process (SGP) has been advancing in order to understand the formation of stream resulting from both surface and subsurface flow comprising Infiltration Excess Overland Flow (IEOF), Saturation Excess Overland Flow (SEOF), Shallow Subsurface Flow (SSF), Direct Precipitation onto Stream Surface (DPOSS), percolation, evapotranspiration and ground water (GW). This paper will only focus on one of the process which is IEOF. Despite the apparent important of IEOF in determining changes in environment, relatively little is understood in the processes that occurred behind. The review aims to minimize the misconception on the terms that regularly used in IEOF studies such as overland flow, surface runoff, urban runoff and stormwater. The term used can make the meaning become misleading and give confusion to the readers. A numerous of terms used to explain the process in Hydrology does not pose problems for Hydrologist but effect the understanding of those who are from different field of background. Besides, this study also discussed on the current model that used in IEOF studies and the trend of integrated hydrological and Geographic Information System (GIS) model in solving IEOF problems. In addition, this paper also concentrates on one of the environmental issues that give impact to IEOF which is global warming.